Effectiveness of non-invasive chromosomal screening for normal karyotype and chromosomal rearrangements - Sun, Bo-lan; Wang, Yong; Sixi-Wen,; Zhou, Liang; Zhang, Chun-hui; Wu, Ze-Xuan; Qiao, Jie; Sun, Qing-yuan; Yao, Ya-xin; Wang, Jing; Yi, Zi-Yun; Qian, Wei-Ping (Frontiers in Genetics, 2023)
Purpose: To study the accuracy of non-invasive chromosomal screening (NICS) results, in normal chromosomes and chromosomal rearrangement groups and to investigate whether using trophoblast cell biopsy along with NICS, to choose embryos for transfer can improve the clinical outcomes of assisted pregnancy. Methods: We retrospectively analyzed 101 couples who underwent preimplantation genetic testing at our center from January 2019 to June 2021 and collected 492 blastocysts for trophocyte (TE) biopsy. D3-5 blastocyst culture fluid and blastocyst cavity fluid were collected for the NICS. Amongst them, 278 blastocysts (58 couples) and 214 blastocysts (43 couples) were included in the normal chromosomes and chromosomal rearrangement groups, respectively. Couples undergoing embryo transfer were divided into group A, in which both the NICS and TE biopsy results were euploid (52 embryos), and group B, in which the TE biopsy results were euploid and the NICS results were aneuploid (33 embryos). Results: In the normal karyotype group, concordance for embryo ploidy was 78.1%, sensitivity was 94.9%, specificity was 51.4%, the positive predictive value (PPV) was 75.7%, and the negative predictive value (NPV) was 86.4%. In the chromosomal rearrangement group, concordance for embryo ploidy was 73.1%, sensitivity was 93.3%, specificity was 53.3%, the PPV was 66.3%, and the NPV was 89%. In group A, 52 embryos were transferred; the clinical pregnancy rate was 71.2%, miscarriage rate was 5.4%, and ongoing pregnancy rate was 67.3%. In group B, 33 embryos were transferred; the clinic pregnancy rate was 54.5%, miscarriage rate was 5.6%, and ongoingpregnancy rate was 51.5%. The clinical pregnancy and ongoing pregnancy rates were higher in the TE and NICS euploid group. Conclusions: NICS was similarly effective in assessing both normal and abnormal populations. Identification of euploidy and aneuploidy alone may lead to the wastage of embryos due to high false positives. More suitable reporting methods for NICS and countermeasures for a high number of false positives in NICS are needed. In summary, our results suggest that combining biopsy and NICS results could improve the outcomes of assisted pregnancy.